2015
DOI: 10.1111/jbi.12697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phylogeographical structures of a lichen‐forming fungus and its green algal photobiont in western North America

Abstract: Aim Lichens comprise a symbiosis of two separate taxa that share geographical distribution but not necessarily the same evolutionary history. Comparison of phylogeographical structures of lichen symbionts provides valuable insight about the processes shaping the lichen's biogeographical pattern. In this study, we tested the extent to which the shared distribution of the widespread lichen‐forming fungus Ramalina menziesii and its photobiont Trebouxia decolorans across six major ecoregions reflect parallel genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…This geographic structure mirrors that of the mycobiont. Congruent structure has been also detected in the epiphytic Ramalina menziesii and its photobiont Trebouxia decolorans across ecoregions in western North America (Werth and Sork 2014;Chen et al 2016), and between Lobaria pulmonaria and its green algal partner (Werth and Scheidegger 2012). Similarly, algal genetic variation in the soil-dwelling Cladonia subtenuis, Thamnolia vermicularis and the bipolar Cetraria aculeata was found to be significantly structured by geography (Yahr et al 2006;Nelsen and Gargas 2009;Fernández-Mendoza et al 2011).…”
Section: Discussionmentioning
confidence: 85%
“…This geographic structure mirrors that of the mycobiont. Congruent structure has been also detected in the epiphytic Ramalina menziesii and its photobiont Trebouxia decolorans across ecoregions in western North America (Werth and Sork 2014;Chen et al 2016), and between Lobaria pulmonaria and its green algal partner (Werth and Scheidegger 2012). Similarly, algal genetic variation in the soil-dwelling Cladonia subtenuis, Thamnolia vermicularis and the bipolar Cetraria aculeata was found to be significantly structured by geography (Yahr et al 2006;Nelsen and Gargas 2009;Fernández-Mendoza et al 2011).…”
Section: Discussionmentioning
confidence: 85%
“…We discovered some similarities in their clustering with certain ecoregions, but overall the phylogenetic trees were largely incongruent among symbionts, suggesting little coevolution between fungal and algal genotypes (90). Next, we compared recent migration patterns for different types of genetic markers to see whether the symbionts were showing similar patterns of movements, which one might expect given that they coexist within the same individual and may respond to climatic fluctuations in a similar way (90). The analysis revealed that the mycobiont and photobiont of lace lichen showed a general tendency to move south, with different patterns of movement across ecoregions for each of the markers (Fig.…”
Section: Case Studies Of Plant Phylogeographymentioning
confidence: 89%
“…First, we compared the genealogical trees from a subset of samples that had mycobiont and photobiont genotypes. We discovered some similarities in their clustering with certain ecoregions, but overall the phylogenetic trees were largely incongruent among symbionts, suggesting little coevolution between fungal and algal genotypes (90). Next, we compared recent migration patterns for different types of genetic markers to see whether the symbionts were showing similar patterns of movements, which one might expect given that they coexist within the same individual and may respond to climatic fluctuations in a similar way (90).…”
Section: Case Studies Of Plant Phylogeographymentioning
confidence: 96%
See 1 more Smart Citation
“…Lichens are formed as a symbiosis between two main partners, a mycobiont and a photobiont. Recent lichen studies strive to integrate both morphological and molecular information from the symbiotic partners (e.g., Chen, Werth, & Sork, ; Fernandez‐Mendoza et al., ; Perez‐Ortega, Ortiz‐Alvarez, Allan Green, & de Los Rios, ; Spribille et al., ; Werth & Sork, ). In this study, we focused our efforts to describe and understand the mycobiont population structure and the associated photobionts in Thamnolia .…”
Section: Discussionmentioning
confidence: 99%